2015
DOI: 10.1111/acer.12781
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traditional and Novel Self-Report Measures to an Alcohol Biomarker for Quantifying Alcohol Consumption Among HIV-Infected Adults in Sub-Saharan Africa

Abstract: Background In sub-Saharan Africa (SSA), HIV-infected patients may under-report alcohol consumption. We compared self-reports of drinking to phosphatidylethanol (PEth), an alcohol biomarker. In particular, we assessed beverage-type adjusted fractional graduated frequency (FGF) and quantity frequency (QF) measures of grams of alcohol, novel non-volume measures, and the Alcohol Use Disorders Identification Test – Consumption (AUDIT-C). Methods We analyzed cohort-entry data from the Biomarker Research of Ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 52 publications
4
38
1
Order By: Relevance
“…In our previous study in this setting, we found only moderate correlation between self-reported measures of drinking and PEth [22]. …”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In our previous study in this setting, we found only moderate correlation between self-reported measures of drinking and PEth [22]. …”
Section: Discussionmentioning
confidence: 72%
“…Both studies were prospective observational cohorts of HIV-infected adults at the Immune Suppression Syndrome (ISS) clinic in Mbarara, Uganda. ADEPT’s aim was to determine the effect of alcohol consumption on pre-ART HIV disease progression; BREATH aimed to describe changes in alcohol consumption during the first year of HIV care [22, 27, 28]. Eligibility criteria for both cohorts included: HIV-infected adult (age ≥ 18), enrolled into care at the ISS clinic and not yet on ART, fluent in English or Runyankole (the local language), living within 60km of the clinic, and for BREATH only, new to the ISS Clinic and HIV care, and reporting past-year alcohol use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations